Prospect of Hydrogen Usage in the Industrial Sector: Thailand Context - Nakapreecha, Nitida; Pongthanaisawan, Jakapong; Wangjiraniran, Weerin; Vivanpatarakij, Supawat; Audomvongseree, Kulyos (International Journal of Energy Economics and Policy, 2023)
Hydrogen is receiving attention as a highly clean alternative energy with the potential to replace conventional fuels. However, it is still more expensive than fossil fuels. Using hydrogen in the energy sector will certainly affect energy costs, which for the private sector is an important factor when making decisions about fuel replacement. The objective of this study is to analyze the financial and economic feasibility of using hydrogen as a fuel in the industrial sector. From the financial and economic analysis, hydrogen can be mixed with natural gas in a ratio of no more than 20 percent by volume and used as fuel in industrial plants that previously used liquefied petroleum gas (LPG) and fuel oil and are within 50 kilometers of a natural gas and hydrogen (NG&H2) mother station. Despite the financial and economic viability, government support is still needed to stimulate the use of hydrogen. The supports include introducing hydrogen to prospective users and ensuring the security of supply; encouraging domestic hydrogen production as well as research and development; developing the necessary infrastructure; and improving regulations and standards to support the supply and use of hydrogen all along the value chain.